If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24x + 13 = 34 Reorder the terms: 13 + 24x = 34 Solving 13 + 24x = 34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 24x = 34 + -13 Combine like terms: 13 + -13 = 0 0 + 24x = 34 + -13 24x = 34 + -13 Combine like terms: 34 + -13 = 21 24x = 21 Divide each side by '24'. x = 0.875 Simplifying x = 0.875
| 3(1x+2)=24 | | -76=8+7x | | (8X+1)(16X-13)=0 | | 5x+15=x+7 | | 9w-w=4+12 | | x/-4=-4-(-5) | | -3(6x+2)=-78 | | -3x-13=x+23 | | x^3+2x^2-11x-12=x+4 | | 12x^5+20x^4= | | -1+x=4x-34 | | x+(x-300)=300 | | -x-8=x+10 | | 9x^3/12x^4 | | x*2=100 | | 2u+2v-4(2-4v+7w)= | | -20a^3b^2+24ab= | | 9y-3=5(y-3) | | x(6x-4)=(6x+8)(x-6) | | 8x^2-[7x-(x^2-x+5y)]+(2x-3y)= | | -2x-2=x+1 | | 14x+13=13x+3 | | (16X-13)=0 | | -x+37=2x+13 | | x^2+y^2+2x+10y+17=0 | | x(6x-4)=(6x+8)(6x-6) | | y=(-1/3x)-2 | | U/3=9.6 | | 14v-14v=-10 | | 1+0,5x=x | | 4x^3-18x^2-10x=0 | | 5-3m+(4m-1)= |